2018
DOI: 10.1080/09654313.2018.1435631
|View full text |Cite
|
Sign up to set email alerts
|

Experimental governance: the role of municipalities in urban living labs

Abstract: Innovations in urban governance such as Urban Living Labs (ULL) are expected to accelerate the transition towards more sustainable and climate-resilient cities. This article reviews different ULL across Europe and explores the role and potential capacity of municipalities in the development of and/or facilitation of ULL as a form of experimental governance. It focuses on the role of the public sector in the multi-actor collaborations that often characterize experimental governance. The article draws on literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 32 publications
(38 reference statements)
0
84
0
1
Order By: Relevance
“…Examples include Amsterdam Smart City (Raven et al ) and the Pecan Street Smart Grid project in Austin, Texas (McLean et al ). Cities have also led the way in creating experimentation platforms such as living labs (Tukiainen et al ; Gascó ; Kronsell and Mukhtar‐Landgren ; Raven et al ). Examples include the Ghent Living Lab (Baccarne et al ), Rotterdam's BlueCity Lab, and the Malmö Innovation Platform (von Wirth et al ).…”
Section: A Typology Of Governance Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples include Amsterdam Smart City (Raven et al ) and the Pecan Street Smart Grid project in Austin, Texas (McLean et al ). Cities have also led the way in creating experimentation platforms such as living labs (Tukiainen et al ; Gascó ; Kronsell and Mukhtar‐Landgren ; Raven et al ). Examples include the Ghent Living Lab (Baccarne et al ), Rotterdam's BlueCity Lab, and the Malmö Innovation Platform (von Wirth et al ).…”
Section: A Typology Of Governance Platformsmentioning
confidence: 99%
“…Innovation platforms sponsored by the public sector may facilitate not only public and private innovation (Kilelu et al 2013) but also open innovation (Hilgers and Ihl 2010;Almirall et al 2014;Brunswicker and Johnson 2015;Tukiainen et al 2015;Ojasalo and Kauppinen 2016;Raunio et al 2016;Mergel 2018). Living labs and smart city platforms potentially magnify the impact of urban experimentation (Baccarne et al 2014;Gascó 2017;Kronsell and Mukhtar-Landgren 2018;Nesti 2018;von Wirth et al 2019) and collaborative platforms may encourage the scaling up of collaborative governance (Ansell and Gash 2017).…”
Section: Why Are Governance Platforms Potentially Important?mentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of 627 urban experiments aimed at addressing climate change all around the world, Bulkeley and Castán Broto (2013) found that local governments were leading 66% of them. In 50-case study of urban living labs across Europe, Kronsell and Mukhtar-Landgren (2018) showed that municipalities have the power to facilitate urban sustainability through experimental governance.…”
Section: Local Experimentsmentioning
confidence: 99%
“…Experience and knowledge gained in intentional communities cannot be transferred one-to-one but have to be adapted within different contexts (e.g., urban neighborhoods and rural municipalities). Insights from intentional communities could, e.g., be taken up by experimental initiatives in urban contexts, such as urban living labs and urban laboratories [74][75][76]. Some future work and support is needed to translate particular low-carbon innovations and infrastructures, derived from intentional communities that allow for the development of more sustainable practices and for novel ways of organizing, e.g., food and shopping practices, into different contexts.…”
Section: Recommendations For Policymakers To Support Community-based mentioning
confidence: 99%